CONSTITUTIONAL JUSTICE PROCEDURE LAW AS A BRANCH OF LAW: THEORETICAL ASPECTS - Pūraitė-Andrikienė, Dovilė (Teisė, 2015)
The advent of constitutional review and the growth of constitutional jurisprudence and its significance to the whole Lithuanian legal system should require detailed analysis of procedures by which the Constitutional Court examines the constitutionality of legislation and other matters falling within its competence, however the legal mind tends to pay relatively little attention to the constitutional justice procedure giving the priority to the look “from the outside” – a final act of a Constitutional Court, but not to the look “from the inside” – a procedure by which the final act is adopted. Thus in the numerous scholarly legal literature about the Constitutional Court there are relatively few research articles dedicated to the issues of constitutional justice procedure. One of the main reasons why these issues are left aside, like not requiring more scientific knowledge, is some uncertainty regarding the position from which they should be dealt with. There is no theoretical consensus about the question, whether legal norms and other provisions governing the procedures by which the Constitutional Court examines the constitutionality of legislation and other matters falling within its competence, to be considered as forming any independent part of the legal system. If so, whether this part of the legal system can be titled a branch of law? This article seeks to prove that constitutional justice procedure law, as a separate procedural branch of law, is substantiated not only by interfaces with other procedural branches of law, but also by the fact, that this area of law is governed by ordinary law acts and therefore can not be considered a procedural segment of the constitutional law. The autonomy of this branch of law is also evidenced by 2 classic features of separation of branches of law: separate legal subject matter and method. Although constitutional justice procedure law, as separate branch of law, can not be accepted without some doubt, especially given the fact that other procedural branches of law are characterized by a far greater intensiveness of regulation, however this branch of law is growing due to the Constitutional Court‘s development of its jurisprudence. This article also draws attention to the fact, that formation of this branch of law has not only a theoretical, but also a practical significance – it would attract more attention of the legal mind to the issues of constitutional justice procedure and provide systematic approach to the problematic aspects of this process and comprehensive discussions will certainly serve the development of constitutional justice procedure in Lithuania.